LONG-TERM SETTLEMENT BEHAVIOR OF MULTI-STORY BUILDINGS ON SOFT SUBSOIL IN SHANGHAI - J. J. Chen; J. H. Wang; S. L. Shen; H. B. Zhou (Lowland Technology International, 2005)
The soft deposit in Shanghai is a multilayered formation due to different sedimentary environments and eras. This soft deposit has high compressibility, and the buildings on it undergo long-term settlement. Most of the multistory buildings in Shanghai are built on natural soft subsoil with a shallow foundation. This paper presents the settlement behavior of 50 multi-story buildings based on long-term observed data. According to the characteristics of the soil profile in various areas, the subsoil condition is categorized into four zones: “hard” Zone, “normal” Zone, “soft” Zone, and “very-soft” Zone. The results of observations of settlement on these four types of subsoil over a long term are presented and compared. Statistical analysis is employed to analyze the observed settlement of various subsoils, including final settlement and the developing process of settlement. In order to investigate the effect on settlement behavior of the thickness of very soft clay layers in the four zones, the relationship between the thickness ratio of soft clay layer Rs and the long-term settlement of buildings is obtained through an analysis of all records. With the increase of Rs, the final settlement and settlement duration increase; however, the settlement during construction decreases. These results can be applied in research on the settlement mechanism and can be used to judge the possible settlement range and provide a design scheme for multi-story buildings in the soft clay region.